Take Advantage of Lessons Learned During the Pandemic - Burke, Darcy (Opflow, 2020)
The COVID‐19 pandemic has had wide‐ranging effects on the water industry, but now you and your colleagues are getting your utility back to “normal,” whatever normal now means. As of this writing in mid‐May, events are still moving unexpectedly and unevenly, so some things still can't be predicted. However, the fundamentals still apply. You need to ensure employee health and safety, your customers require attention, and operations need to continue.